Clinical significance of residual viremia detected by two real-time PCR assays for response-guided therapy of HCV genotype 1 infection - Vermehren, Johannes; Aghemo, Alessio; Falconer, Karolin; Susser, Simone; Lunghi, Giovanna; Zeuzem, Stefan; Colombo, Massimo; Weiland, Ola; Sarrazin, Christoph (Journal of hepatology, 2014)
The duration of current standard dual and protease inhibitor-based triple therapies for chronic hepatitis C is determined by assessment of early viral kinetics. Little is known about differences between HCV RNA assays for the use in response guided therapy. HCV RNA was assessed by two widely used real-time PCR-based assays, Cobas Ampliprep/Cobas TaqMan (CAP), and Real-Time HCV (ART) in 903 samples of hepatitis C genotype 1 patients treated with dual (n=169) or telaprevir-based triple therapy (n=164) in three European countries. Overall, CAP and ART were in excellent agreement for the determination of HCV-RNA concentrations (mean difference 0.21 log10 IU/ml). For treatment-naïve patients treated with peginterferon-alfa and ribavirin a lower rate of undetectable HCV-RNA at week 4 (RVR) was observed for ART (9%) vs. CAP (16%). Although 11/27 (41%) of patients with shortened treatment (24weeks) had detectable HCV-RNA <12IU/ml by ART at week 4 none of these patients experienced virologic relapse after treatment cessation. In patients who received triple therapy, 67% and 37% had undetectable HCV-RNA at week 4 by CAP and ART, respectively. However, 18/31 (58%) eligible patients for shortened treatment based on CAP had detectable HCV-RNA by ART at week 4. Again, relapse was not observed in these patients. Lower rates of undetectable HCV-RNA at week 4 were observed with ART compared to CAP in patients treated with dual and triple therapies. For ART, detectable <12IU/ml HCV-RNA levels at week 4 may be sufficient as part of the criteria used for selecting patients who receive a shortened treatment regimen.